2006
DOI: 10.1111/j.1750-3639.2005.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Meningioangiomatosis with and without Meningioma: A Clinicopathologic and Genetic Series of 24 Cases with Review of the Literature

Abstract: Meningioangiomatosis (MA) is a rare seizure-associated lesion of presumed hamartomatous or developmental origin. It is occasionally combined with a neoplasm, most commonly meningioma (MA-M). In the current study, we examined 24 cases (14 pure MA, 10 MA-M) using immunohistochemistry for merlin, protein 4.1 B, progesterone receptor (PR), and MIB-1, as well as FISH for NF2 and 4.1B gene dosages. Nine cases of MA-M (90%) had gene deletions (NF2/4.7B), protein losses (merlin/protein 4.1B), and/or PR positivity, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 72 publications
(60 reference statements)
4
51
0
5
Order By: Relevance
“…Occasionally, sporadic MA combines with a neoplasm, most commonly meningioma (MA-M) [2]. MA is usually considered a benign, nonneoplastic lesion, while genetic and molecular studies have suggested that MA-M may be a neoplasm [3][4][5]. Given the neoplastic nature of MA-M, it is reasonable to assume that the clinical features of MA-M may be different from those of pure MA.…”
Section: Introductionmentioning
confidence: 97%
“…Occasionally, sporadic MA combines with a neoplasm, most commonly meningioma (MA-M) [2]. MA is usually considered a benign, nonneoplastic lesion, while genetic and molecular studies have suggested that MA-M may be a neoplasm [3][4][5]. Given the neoplastic nature of MA-M, it is reasonable to assume that the clinical features of MA-M may be different from those of pure MA.…”
Section: Introductionmentioning
confidence: 97%
“…These tumors should not be viewed as meningioma with brain invasion corresponding to WHO grade II [ 227 ]. Although a correlation of prognosis with WHO histologic grade exists, the correlation is not is strong as in adult cases.…”
Section: Meningiomamentioning
confidence: 88%
“…Although these tumors are intraparenchymal, they should not be viewed as brain invasion [ 227 ]. These tumors radiographically and pathologically mimic invasive meningiomas [ 227 ]. The meningioangiomatosis component in cases associated with meningioma appears to be neoplastic in nature in comparison to cases of pure meningioangiomatosis [ 227 ].…”
Section: Meningioangiomatosismentioning
confidence: 95%
See 1 more Smart Citation
“…Meningioangiomatosis is a rare disorder marked by a proliferation of blood vessels surrounded by collars of meningothelial cells. There is an association of the entity with neurofibromatosis type II and with overlying meningiomas [32]. Again, the phenotypic appearance of the FCD adjacent to these lesions most commonly resembles the type I FCD patterns; although the type IIa pattern has been described in some cases of meningioangiomatosis [5].…”
Section: Ilae Classificationmentioning
confidence: 97%